Analisis Ekonomi dan Sosial Terhadap Kesetaraan Ntar Wilayah di Kota Makassar, Sulawesi Selatan - Revirgin, Fazila Ghani; Maulana, Pradifta Pilar Putra; Wahyuni, Duwi; Wibowo, Danang Avrilio Satria Dava; Putri, Calista Evanya Nafitri; Rahajeng, Anggi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The analysis addresses regional equality in Makassar City from both economic and social perspectives, focusing on population density, educational infrastructure (number of schools), economic growth, poverty levels, and the open unemployment rate. Although Makassar has experienced rapid economic growth particularly as the economic center of South Sulawesi, gaps between regions, especially between the city center and suburban areas, still persist. These disparities directly affect the quality of life, exacerbate inequality, and hinder the welfare of affected communities. Policy interventions are essential, such as poverty reduction through skills training, optimization of information technology to enhance transparency and accountability, revitalization of slum areas to reduce environmental impacts, digitization of SMEs to create new jobs in the digital sector, and multi-stakeholder collaboration to ensure effective planning and implementation. These efforts will improve community welfare and foster equality among regions, serving as a tangible step toward sustainable development.